Anti-oxidant and anti-inflammatory effects of caffeic acid: in vivo evidences in a model of noise-induced hearing loss. (September 2020) - Paciello, Fabiola; Di Pino, Antonella; Rolesi, Rolando; Troiani, Diana; Paludetti, Gaetano; Grassi, Claudio; Fetoni, Anna Rita
Abstract: Scope: The imbalance of cellular redox status, in conjunction with the activation of inflammatory processes, have been considered common predominant mechanisms of noise-induced hearing loss. The identification of novel natural products as potential therapeuticstargeting oxidative stress and inflammatory pathways is an emerging field. Here, we focused on the polyphenol caffeic acid (CA), the major representative of hydroxycinnamic acids and phenolic acid, in order to investigate its protective capacity in a model of sensorineural hearing loss induced by noise. Methods and results: Hearing loss was induced by exposing animals (Wistar rats) to a pure tone, 120 dB, 10 kHz for 60 min. By using auditory brainstem responses (ABRs) and immunofluorescence analysis, we found that CA protects auditory function and limits cell death in the cochlear middle/basal turn, damaged by noise exposure. Immunofluorescence analysis provided evidence that CA mediates multiple cell protection mechanisms involving both anti-inflammatory and anti-oxidant effects by decreasing NF-κB and IL-1β expression in the cochlea and opposing the oxidative/nitrosative damage induced by noise insult. Conclusions: These results demonstrate that the supplementation of polyphenol CA can be considered a valid therapeutic strategy for attenuating noise-induced hearing loss and cochlear damage targeting both inflammatory signalling and cochlear redox balance. Graphical abstract: Image 1 Highlights: Cross-talk between oxidative and inflammatory pathways represents a target for NIHL treatment. CA administration decrease cochlear superoxide and lipid peroxidation expression in NIHL. Cochlear increased expression of inflammatory markers is counteracted by CA. CA administration contributes to the recovery of auditory function in NIHL.